2002
DOI: 10.1097/00002826-200201000-00007
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Properties of Pentoxifylline, Piracetam, and Vinpocetine

Abstract: Oxygen-free radicals play an important role in several physiologic and pathophysiologic processes. In pathologic circumstances, they can modify and damage biologic systems. Because oxygen-free radicals are involved in a wide range of diseases (cerebrovascular, cardiovascular, etc.), scavenging these radicals should be considered as an important therapeutic approach. In our in vitro study, we investigated the antioxidant capacity of three drugs: pentoxiphylline (Sigma Aldrich, St. Louis, MO, USA) piracetam (Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 29 publications
3
51
1
1
Order By: Relevance
“…It is somewhat harder to predict, with respect to therapeutic efficacy, the relative contribution of sodium channel block compared with the many other pharmacological actions of the drug. However, similar potencies have been claimed for an antioxidant action (Horvath et al, 2002) and phosphodiesterase E-1 inhibition (Chiu et al, 1988), suggesting that sodium channel block may impart a significant contribution to overall efficacy (Bonoczk et al, 2000). In summary, the present data demonstrate that vinpocetine is capable of blocking rNa V 1.8 sodium channels at concentrations that may be therapeutically relevant.…”
supporting
confidence: 82%
“…It is somewhat harder to predict, with respect to therapeutic efficacy, the relative contribution of sodium channel block compared with the many other pharmacological actions of the drug. However, similar potencies have been claimed for an antioxidant action (Horvath et al, 2002) and phosphodiesterase E-1 inhibition (Chiu et al, 1988), suggesting that sodium channel block may impart a significant contribution to overall efficacy (Bonoczk et al, 2000). In summary, the present data demonstrate that vinpocetine is capable of blocking rNa V 1.8 sodium channels at concentrations that may be therapeutically relevant.…”
supporting
confidence: 82%
“…It was stated that PTX might be beneficial in endotoxaemia (Krysztopik et al 2000) and PTX increased the survival time in severe endotoxaemia of rats (W u et al 1999). However, it was stated that PTX did not have significant antioxidant capacity at therapeutic concentrations, but increasing their concentrations led to a significant scavenger effect in humans (Horvath et al 2002). As a result, PTX may be beneficial in endotoxaemia, but its antioxidant effect may be depend on dose, administration route and animal species.…”
Section: Resultsmentioning
confidence: 99%
“…Several in vitro studies have confirmed the potential antioxidant effects of this drug. [30,31] The aim of our experimental investigation was to determine the eventual preventive effects of pentoxifylline on gentamicin-induced acute renal failure in rats.…”
mentioning
confidence: 99%